STUDY OF HETEROSIS AND COMBINING ABILITY IN EXOTIC AND INDIGENOUS CROSSES OF BARLEY (HORDEUM VULGAR L.) UNDER RAINFED ENVIRONMENT - A. H. MADAKEMOHEKAR,; L. C. PRASAD,,; J. P. LAL,,; S. S. BORNARE,; R. PRASAD, (The Bioscan, 2015)
Ten selected exotic barley lines were crossed with each of four testers in a line × tester design to evaluate combining ability and heterosis, for yield and its component traits to identify promising hybrids of barley under drought condition.The mean squares forgeneral combining ability (GCA) and specific combining ability (SCA) effects were highly significant for all the traits studied. Among the parents, testers namely, BH 902 and RD 2508 and lines Priestige, Athoulpa, Marriya and Kheel were good general combiners for grain yield and its component traits. On the basis of SCA effects, Marriya X BH 902, Athoulpa X RD 2508, Himani X RD 2508, Yardu X Lakhan, Morac-9-75 X RD 2508 and Prestige X Lakhan for grain yield were observed as most promising crosses. While,Marriya X BH 902, V Morles X BH 902, Prestige X Lakhan and Yardu X Lakhanwere recorded highest magnitude of economic heterosis over standard check K- 603 for grain yield, which might be of practical use in barley improvement programme under rainfed environment.